Recepcja i wpływy Eugeniusza Sue we Włoszech = Reception and influence of Eugene Sue in Italy - Tichoniuk-Wawrowicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The nineteenth century witnessed a rapid development of popular fiction. Growing number of nondemanding readers allowed authors to support themselves and gain popularity without old-timepatronage. Therefore, industrial literature ("literature industrielle") flourished, often taking the form ofa serial novel ("roman feuilleton"; "romanzod` appendice"). Such as "The Mysteries of Paris" ("Les Mysteres de Paris"; 1842-1843) by Eugene Sue.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); krytyka literacka włoska; 19 w.